Scalable Uncertainty Management 5th International Conference, SUM 2011, Dayton, OH, USA, October 10-13, 2011. Proceedings - Benferhat, Salem; Grant, John.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 5th International Conference on Scalable Uncertainty Management, SUM 2011, held in Dayton, OH, USA, in October 2011. The 32 revised full papers and 3 revised short papers presented together with the abstracts of 2 invited talks and 6 (3z(Bdiscussant(3y (Bcontributions were carefully reviewed and selected from 58 submissions. The papers are organized in topical sections on argumentation systems, probabilistic inference, dynamic of beliefs, information retrieval and databases, ontologies, possibility theory and classification, logic programming, and applications.s
Keywords: Computer science; Computer communication systems; Database management; Data mining; Information storage and retrieval; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; Computer Communication Networks; Database Management; Data Mining and Knowledge Discovery; Electronic books